2017
DOI: 10.1007/s11011-017-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic treatment with quetiapine induces antidepressant-like behavior and exerts antioxidant effects in the rat brain

Abstract: Many studies note that changes in oxidative balance are involved in the pathogenesis of major depressive disorder (MDD) and in the success of some antidepressants. Quetiapine exerts a therapeutic response and induces changes in physiological mechanisms that appear to underlie MDD. The objective of this study was to evaluate the antidepressant and antioxidant effects of quetiapine (20 mg /kg) in adult animals. Sixty minutes after an acute treatment or the last administration of chronic treatment (14 days) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 96 publications
0
11
0
1
Order By: Relevance
“…The detection wavelength was 254 nm and the reference solution of ATP prepared according to the dissolving standard. Results expressed as nM/mg protein [71].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The detection wavelength was 254 nm and the reference solution of ATP prepared according to the dissolving standard. Results expressed as nM/mg protein [71].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…34,35 Interestingly, next study showed that the antidepressant therapy caused a reduction myeloperoxidase activity in the amygdala, hippocampus, amygdala and prefrontal cortex while SOD and CAT activity is believed to increase in nucleus accumbens of rat brain after antidepressant therapy. 36 Another important oxidative enzyme associated with depression is xanthine oxidase (XO); a post-mortem study had shown an increased level of XO in serum and the thalamus. 37,38 In addition, patients with depression have been characterized by decreased levels of vitamin E, vitamin C, zinc, uric acid, coenzyme Q10 and glutathione (GSH), although the latter did not change following electroconvulsive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found that administration of venlafaxine to stressed animals significantly elevated the level of CAT protein in their midbrain and cerebral cortex. Similarly, catalase activity increased in the nucleus accumbens of rat brains after administration of quetiapine, an atypical antipsychotic used also in the pharmacotherapy of depression 36. In addition, a study employing a model of behavioural despair in mice showed that venlafaxine restored reduced CAT activity in the brain 41.…”
mentioning
confidence: 97%
“…Quetiapine may also be an effective antioxidant. Across two studies in mice, acute and chronic quetiapine increased mitochondrial respiratory chain activity and reduced markers of oxidative stress in the prefrontal cortex, nucleus accumbens, amygdala and hippocampus (Ignacio et al, ; Ignácio et al, ).…”
Section: Resultsmentioning
confidence: 99%